Commentary: Study of gene–environment interplay – a lesson in how to keep oneself busy for the foreseeable future. (5th September 2013) - Viding, Essi
Abstract : Psychologists and psychiatrists have long been aware that individuals differ in their response to environmental stressors. It is equally apparent that whilst positive or corrective environmental factors help some individuals, others seem to benefit little, if at all. To make the matters even more interesting (at least for a researcher who is hoping for a long and painstaking road of scientific discovery), it is not safe to assume that environments operate entirely independently of the study participants.